Hereditary xanthinuria in a goat. (13th February 2019) - Vail, Krystal J.; Tate, Nicole M.; Likavec, Tasha; Minor, Katie M.; Gibbons, Philippa M.; Rech, Raquel R.; Furrow, Eva
Abstract : A 2‐year‐old mixed breed goat was presented for a 1‐day history of anorexia and 1 week of weight loss. Serum biochemistry disclosed severe azotemia. Abdominal ultrasound examination showed decreased renal corticomedullary distinction, poor visualization of the renal pelves, and dilated ureters. On necropsy, the kidneys were small, the pelves were dilated, and the medulla was partially effaced by variably sized yellow nephroliths. Histologically, cortical and medullary tubules were distended by yellow‐brown, multilayered crystals. Stone composition was 100% xanthine. Exonic sequencing of xanthine dehydrogenase ( XDH ) and molybdenum cofactor sulfurase ( MOCOS ) identified 2 putative pathogenic variants: a heterozygous XDH p.Leu128Pro variant and a homozygous MOCOS p.Asp303Gly variant. Variant frequencies were determined in 7 herd mates, 12 goats undergoing necropsy, and 443 goats from genome databases. The XDH variant was not present in any of these 462 goats. The MOCOS variant allele frequency was 0.03 overall, with 3 homozygotes detected. Hereditary xanthinuria is a recessive disorder in other species, but the XDH variant could be causal if the case goat is a compound heterozygote harboring a second variant in a regulatory region not analyzed or if the combination of the XDH and MOCOS variants together abolish XDH activity. Alternatively, the MOCOS variant alone could be causal despite the presence of other homozygotes, because hereditary xanthinuria in humans often is asymptomatic. Ours is the first report describing the clinical presentation and pathology associated with xanthine urolithiasis in a goat. The data support hereditary xanthinuria, but functional studies are needed to conclusively determine the causal variant(s).